Studi Kasus Tentang Kinerja Karyawan Kelurahan Di KecamatanTegal Timur - Sri Adi Nurhayati; Sesya Dias Mumpuni (Universitas Pancasakti Tegal, 2018)
Procrastination is the behavior of delaying work, which directly affects employee performance. Employee performance is seen from the results of their work in quality and quantity in accordance with the duties and responsibilities given to them. The purpose of this study was to increase community satisfaction with the performance of kelurahan employees in the sub-district of Tegal Timur. The method that will be used in achieving the goal is the mix method. The use of data qualitatively by using case studies, then carried out a quantitative approach that was used as a calculation of the scale of work procrastination and the performance of kelurahan employees in the sub-district of Tegal Timur. Within a period of six months it was expected that there had been a change in the performance of the kelurahan employees in Tegal Timur sub-district through Rational Emotive techniques and Cognitive Behavior, the data obtained could represent the performance conditions of kelurahan employees in Tegal Timur sub-district. The level of community satisfaction with the performance of kelurahan employees in Tegal Timur sub-district increased by 5%.